Sosialisasi Microgreen sebagai Pengenalan Bentuk Budidaya Sayuran Urban Farming di Desa Sarirogo Sidoarjo - Alif Galih Baskoro; Virania Azzahra Putri; Haninda Aulia Putri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Kuliah Kerja Nyata (KKN) is a program carried out by universities as an implementation of the Tri Dharma Perguruan Tinggi. KKN aims to apply knowledge and theory during lectures by providing support to the community in managing local resources. The Covid-19 pandemic has affected various sectors of life. One sector that experienced a very large impact was the economic sector. Sidoarjo Regency is one of the districts with high positive cases of Covid-19 and has become a red zone. Based on the survey results, it was found several problems caused by the Covid-19 case, namely the economic impact, especially the MSME actors who have an important role for the economy in the Sarirogo village, Sidoarjo Regency. The pandemic has also resulted in restrictions on activities outside the home. So we need a solution so that people can still meet their needs. One solution is to develop urban farming vegetable cultivation, namely microgreen. The purpose of this microgreen socialization is expected to be able to provide education to Sarirogo villagers about how to cultivate microgreen vegetables, help solve problems that arise from microgreen vegetable cultivation activities and optimize the use of vacant land so that it can provide a nutritious food source. The output is a microgreen socialization video and its stages as well as a training module. The existence of this socialization increases public knowledge about the form of urban farming, especially microgreen vegetable cultivation.